Fait/événement - Document/monument - Giuseppe Di Liberti (Images Re-Vues)
In our ordinary experience, facts (that we know and say about the events, our descriptions, our versions) are clearly distinguished from events, and their inclusion in the catalogue of the world is controversial. Works of art, however, exhibit a construction of facts and the possibility of a singular event. How this coexistence sketches a particular temporality of the artistic object? How the couple fact/event can find his form by the couple document/monument?